2018
DOI: 10.1016/j.srhc.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating and supporting HIV+ parenthood: Lessons for developing the advocate role of voluntary HIV support services workers

Abstract: The role of HIV support workers is important in facilitating access to resources and complex systems. HIV support workers should be recognised and as they are often a trusted professional to address stigma, discrimination and barriers to services. The study contributes to research seeking to understand the emerging needs and support requirements for people living with HIV seeking fertility and adoption. Further work in this area is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Studies about experiences. Of the 23 studies about experiences with peer support, 15 concerned experiences with providing peer support (Table 1; studies 2, 4, 5, 7-9, 15-23), [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] four addressed experiences with receiving peer support (Table 1, studies 1, 6, 11, 13), [50][51][52][53] and four explored PLHIV's views on both providing and receiving peer support (Table 1, studies 3, 10, 12, 14). [54][55][56][57] Most studies (n = 20, 59%) utilized a qualitative design (Table 2).…”
Section: Categories Of Studies and Their Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies about experiences. Of the 23 studies about experiences with peer support, 15 concerned experiences with providing peer support (Table 1; studies 2, 4, 5, 7-9, 15-23), [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] four addressed experiences with receiving peer support (Table 1, studies 1, 6, 11, 13), [50][51][52][53] and four explored PLHIV's views on both providing and receiving peer support (Table 1, studies 3, 10, 12, 14). [54][55][56][57] Most studies (n = 20, 59%) utilized a qualitative design (Table 2).…”
Section: Categories Of Studies and Their Resultsmentioning
confidence: 99%
“…With respect to the results, nine studies reported that peer supporters provided practical, informational, emotional, and/or social support (studies 4, 5, 7, 9, 10, 12, 14, 17, 23) 36 38 , 40 , 43 , 49 , 55 57 and modeled healthy behavior (studies 8, 9, 17). 39 , 40 , 43 Studies have shown that peer supporters feel empowered in their own lives, have different motivations (such as being a role model and helping others), learn new skills and share knowledge, gain self-awareness, and become more visible in the community.…”
Section: Resultsmentioning
confidence: 99%
“…It is argued that people living with HIV approaching adoption services uphold resilient qualities reported in the above studies. Often, they have worked hard to invest in support or helping services and coping strategies, which enables them to respond well to future life challenges (Cane, 2018), although this does not necessarily mean that every person with HIV seeking to adopt is resilient enough to do so.…”
Section: Individual Strengthsmentioning
confidence: 99%
“…As a severe disease, HIV is a critical matter due to its many complications, such as mortality, high financial costs caused by treatment and care, social and psychological problems like depression, and many other issues (Cane, 2018). There has been an increase in the number of patients with HIV whose risky behaviors play a vital role in this trend (King & Winchester, 2018).…”
Section: Introductionmentioning
confidence: 99%